Beyond Economic Base Theory: The Role of the Residential Economy in Attracting Income to Swiss Regions - Segessemann, Alain; Crevoisier, Olivier (My University, 2015)
Regional development theories are mainly focused on export-based activities to explain regional competitiveness. The increasing mobility of workers and residents leads to a reconsideration of this approach. Residential economy has become a strategic issue to generate incomes within regions. With this view, the paper analyses the link between economic activities and incomes from workers and annuitants residents. A spatial typology breakdown is compiled for Swiss regions using a hierarchical cluster analysis (HCA). Empirical results highlight various regional development profiles. Conversely to export-based theories, regions with higher income are those with strong residential economy, thus opening new avenues for local governance.
Keywords: Regional development; Residential economy; Export-based economy; Regional income; Switzerland